THE CONCEPTS OF PERSONALITY AND SPIRITUALITY DEVELOPMENT IN PSYCHOLOGY : (Study Of Analysis Perspective Badi'uzzaman Said Nursi) - Arroisi, Jarman; Fadhilah, Manzilatul (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
A recent discovery in psychology that is very amazing is that the central brain is active when a person's personality and spirituality can function as a balancer between the roles of the soul and the physical. In this context, Badiuzzaman Said Nursi initiated a concept of how to develop the development of one's personality and spirituality in psychology as a solution to the problems faced by humanity today in the form of globalization, westernization, secularization and liberalization which makes humans lose direction and grip on life. Therefore, human personality and spirituality are easily swayed. This research is a qualitative research, by taking library data as the object of research. The library data is in the form of books by Badiu'zzaman Said Nursi, as well as research works or notes that help in concluding the concept of personality development and spirituality in psychology from the perspective of Badiu'zzaman Said Nursi. Furthermore, using descriptive-analytic method as an analytical knife in drawing conclusions. The results of this study are that the development of a person's personality and spirituality cannot be separated from religious and divine aspects. According to Badiuzzaman Said Nursi, the concept of the development of one's personality in psychology is divided into four ways, namely: (1) Confession of one's helplessness before God Almighty, (2) Confession of self-poverty towards God Almighty, (3) Expecting God's love , (4) Doing reflection or meditation. While the concept of developing one's spirituality in psychology is also divided into four ways, namely: (1) Through the light of faith in God, (2) Through holistic devotion (worship) to God, (3) Manifesting God's asthma that is reflected in them, and (4) Following the way of the Qur'an or the way of nature. Sebuah penemuan terbaru dalam ilmu psikologi yang sangat mengagumkan adalah bahwa sentral otak bersifat aktif apabila kepribadian dan spiritualitas seseorang dapat berfungsi sebagai penyeimbang antara peran jiwa dan fisik. Dalam konteks ini, Badiuzzaman Said Nursi menggagas sebuah konsep bagaimana mengembangkan perkembangan kepribadian dan spiritualitas seseorang dalam ilmu psikologi sebagai solusi problematika yang dihadapi oleh umat manusia masa kini berupa arus globalisasi, westernisasi, sekularisasi, dan liberalisasi yang menjadikan manusia kehilangan arah dan pegangan hidup. Karenanya, kepribadian dan spiritualitas manusia mudah terombang ambing. Penelitian ini merupakan penelitian kualitatif, dengan mengambil data-data kepustakaan sebagai obyek penelitian. Data pustaka tersebut berupa buku-buku karya Badiuzzaman Said Nursi, serta karya-karya penelitian atau catatan-catatan yang membantu dalam menyimpulkan konsep perkembangan kepribadian dan spiritualitas dalam ilmu psikologi perspektif Badiu'zzaman Said Nursi. Selanjutnya menggunakan metode deskriptif-analitik sebagai pisau analisis dalam mengambil kesimpulan. Adapun hasil dari penelitian ini adalah, perkembangan kepribadian dan spiritualitas seseorang tidak dapat dilepaskan dari aspek religi dan ketuhanan. Menurut Badiuzzaman Said Nursi, konsep perkembangan kepribadian seseorang dalam ilmu psikologi terbagi menjadi empat cara, yaitu: (1) Pengakuan ketidakberdayaan seseorang di hadapan Tuhan Yang Maha Esa, (2) Pengakuan kemiskinan diri terhadap Tuhan Yang Maha Esa, (3) Mengharapkan cinta Tuhan, (4) Melakukan refleksi atau meditasi. Sedangkan konsep perkembangan spiritualitas seseorang dalam ilmu psikologi terbagi menjadi empat cara juga, yaitu: (1) Melalui cahaya keimanan kepada Tuhan, (2) Melalui pengabdian secara holistik (ibadah) kepada Tuhan, (3) Memanifestasikan asma Allah yang terefleksi dalam diri mereka, dan (4) Mengikuti jalan al-Qur’an atau jalan hakikat.